Sounding out a continent: seven decades of bioacoustics research in Africa. Issue 6 (2nd November 2022) - Becker, Frowin K.; Shabangu, Fannie W.; Gridley, Tess; Wittmer, Heiko U.; Marsland, Stephen
ABSTRACT: Bioacoustics has emerged as a useful method of data collection and analysis for diverse animals in a wide range of environments and has helped to describe, monitor, and conserve some of Africa's species biodiversity. However, little is known about how much it contributes to the continent's research corpus. We report results from a systematic review of bioacoustics applications in Africa that summarises the current state of the field and identifies research opportunities. Using keyword searches of bibliographic databases, scanning reference lists, and placing appeals to the bioacoustics community in Africa we identified 727 publications between 1953 and mid-2020. We documented variables ranging from publication type and author affiliation, geographic location, biome and habitat, biological groups, and research type. Most (69%) studies were focused on animal behaviour, with terrestrial species (88.6%), particularly mammals, substantially outweighing research on freshwater (4.8%) and marine (6.6%) habitats. The majority (74.3%) of authors who have contributed to this body of knowledge were non-African affiliates. Our review suggests that bioacoustics research in Africa has considerable room to expand institutionally, taxonomically, and thematically. We highlight the need and potential for more locally driven research and provide a roadmap for future bioacoustics applications across the continent.